A Comparative Study of Some Kinematic Variables at the Start of Swimming in two Different Ways (Regular Method and Track Method) - Abo-Touq, Iyad Mohmd; Abdel-Fattah, Osama Mahmoud (Dirasat: Educational Sciences, 2020)
This study aims to identify the values ​​of some kinematic variables for the starting stage in two different ways (the normal method, the track method) among Jordanian national team swimmers. It also aims to identify the differences in these values ​​according to the starting method, in addition to the relationship between the swimmer’s speed and the kinematic variables under study. To achieve this goal, the researchers used a descriptive approach on a sample consisting of (6) swimmers in the Jordanian swimming team (age 18.75 ± 0.6 years, length 1.81 ± 3 cm, mass 70.50 ± 0.60 kg, years of experience 6 ± 0.60 years). The study dealt with some kinematic variables for the starting phase, including starting phase time, starting angle, water entry angle and swimmer’s speed. The results of the study showed that the technique of the study sample in the initiation stage was tainted by some errors, but the study sample achieved better results in (7) variables by the track method. There are also statistically significant differences between the two methods in the variables of reaction time, start time and average swimmer speed. In addition, the results of the study showed a statistically significant inverse correlation between swimmer speed, start time and swimmer time under water.